Effects of ChatGPT and Generative Artificial Intelligence in Higher Education: Voices of Jamaican Academic Faculty - Oneil N Madden; Nattalie McKenzie; Jason-Lee Daley (International Journal of Education and Humanities, 2025)
ChatGPT – the more competent non-biological other – continues to dominate discussions across universities worldwide, with varying views posited for both its inclusion and exclusion in the academic space. Over the past year, several Higher Education Institutions (HEIs) have tested and implemented policies to guide the inclusion of artificial intelligence (AI) for academic purposes. However, research and policies on ChatGPT are not advanced in the Jamaican and Caribbean contexts – a gap this study aims to fill. Consequently, this study investigated academic faculty’s knowledge, usage, and perceptions of ChatGPT, AI policies at their institutions, and the direction HEIs could take to develop appropriate guidelines. Thirteen lecturers from six institutions responded to an online questionnaire. The data was analyzed using qualitative content analysis. Findings reveal that, when the data was collected, the majority of the respondents had either basic notions or no knowledge of the characteristics of ChatGPT. Notwithstanding, the chatbot can help students with assignments and assist lecturers with lesson planning, research papers, and personal tasks. It can be a teacher’s assistant to enhance human knowledge. However, ChatGPT could lead to over-dependence and encourage intellectual laziness among students, which calls for lecturers to curtail assessments to focus on higher-order thinking skills. Furthermore, AI policies are lacking in local institutions, a problem that needs to be addressed promptly, and training and sensitization campaigns are necessary to promote ethical usage. The study has implications for AI frameworks in academic contexts